Exploring Plogging’s Usefulness and Feasibility in Schools: Insights from Physical Education Teacher Education Students - Carlos Martínez-Mirambell; Olalla García-Taibo; Andreas Fröberg; Salvador Baena-Morales (Australian Journal of Environmental Education)
Education is essential for addressing the global environmental crisis and engaging students through experiential learning is crucial. In physical education, physical literacy offers a holistic approach to sustainable education, with plogging exemplifying this integration. This study investigates the perceptions of Physical Education Teacher Education (PETE) students regarding the implementation of plogging in school curricula. Using qualitative interviews with 80 PETE students and analysing responses with NVIVO 12 software, the study reveals mixed feelings about this innovative practice. Participants see plogging as valuable for fostering both physical literacy and environmental awareness. However, concerns about feasibility include the need for institutional support, curriculum flexibility and community involvement. These findings highlight the potential of plogging to enhance educational programmes by combining physical activity with environmental stewardship. The results can inform the development of future educational strategies that integrate plogging to promote sustainability and holistic student development.